Don't call me names! - Cole, Joanna; Munsinger, Lynn (New York : Random House, 1990)
Nell is afraid of Mike and Joe because they always tease her and make fun of her, until the day she stands up to them on behalf of her friend Nicky.
Keywords: Behavior -- Fiction; Friendship -- Fiction; Animals -- Fiction